Numerical Investigation of Radiative Heat Transfer inside a 2-D Irregular Geometry Containing Nano- and Micro-size Particles. (February 2019) - Moghadassian, Behnam; Jafari, Mohammad; Hafezisefat, Parinaz; Mirhosseini, Mojtaba; Rezania, Alireza
Abstract: Mie theory is very important in meteorological optics and atmospheric science. In radiative heat transfer, Mie theory is used to assess the heat transfer in participating particulate media. The effect of Mie scattering in a 2D irregular geometry is numerically investigated in this study. The medium participates in the radiative heat transfer and is filled with particulate media. FT n finite volume method is applied to solve the radiative transfer equation numerically. Mie theory is applied for calculation of scattering phase function in particulate media. To discretize the irregular geometries, non-orthogonal mesh is used. To calculate the radiative intensity at the cell faces, the high resolution CLAM scheme is applied. The particulate media contains particles of different sizes, ranging from 250 nanometers to 5 micrometers. Cases of scattering in media with dielectric particles and absorbing particles are considered. Also the influences of the number of particles per unit volume on the dimensionless radiative heat transfer quantities are studied.